Peduli Lingkungan Membangun Karakter Untuk Mengurangi Limbah Plastik - Suryanti, Suryanti; Ferazona, Sepita; Ritawati, Tengku; Nurmalinda; Robiah, Siti; Hajar, Ibnu; Syafitri, Alviany Dwi; Praguna, Edo (UIR Press, 2025)
The implementation of community service activities aims to care for the environment, build character to reduce plastic waste in SMP Negeri 9 Pekanbaru. The method used with the socialization stage, the counseling stage, the stage of implementing the outcome of the service and the monitoring and evaluation stage using an environmental care questionnaire consisting of one indicator, with 8 subindicators and 26 statements using the google form Community service has been carried out on students of SMP Negeri 9 Pekanbaru, in grade VIII with a total of 40 people. The scope of material in this activity about caring for the environment includes; caring, awareness, involvement, responsibility, exemplary, cooperation, courage and social concern. Provided with google form. Data was obtained from a questionnaire that was distributed on average to care for the environment with a score of 79% in the caring category. With the education provided, it is hoped that students can personally build a better character about caring for the environment and can apply it in real life and can be realized in daily behavior. So that becoming more appreciative and loving for the environment can reduce environmental damage that comes from plastic waste pollution. It can be concluded that caring for the environment builds character to reduce plastic waste for students of SMP Negeri 9 Pekanbaru category cares.